Low-Impedance, High Surface Area Pt-Ir Electrodeposited on Cochlear Implant Electrodes. Issue 12 (1st January 2018) - Lee, Curtis D.; Hudak, Eric M.; Whalen, John J.; Petrossians, Artin; Weiland, James D.
Abstract : A high surface area, Pt-Ir coating was electrodeposited onto the contacts of Advanced Bionics HiFocus 1j electrode arrays. The coating was imaged using optical and scanning electron microscopy (SEM) and the impedance was directly measured using clinically relevant voltage transients of biphasic pulses as short as 17 μs. The coating, which SEM showed to completely cover the underlying substrate, decreased the polarization impedance of 17 μs and 32 μs pulses by 91% and 93%, respectively.